PEMANFAATAN LIMBAH BOTOL PLASTIK SEBAGAI MEDIA TANAM HIDROPONIK SISTEM WICK SEDERHANA DI DESA KORLEKO SELATAN - Yadnya, Made Sutha; Maryani, Indah; Zulvia, Ridho; Holis, M. Sopian; Devi, Radhe Vrndavanesvari; Wulandari, Haspita Ariana; Supiana, Wina; Zulhidayati, Masni; Ananda, M. Dimas; Amalia, Annisa Rizki; Apriandi, M. Irawan; Hasnan P, M. Ade Zaini (Jurnal Pepadu, 2025)
This paper discusses the use of plastic bottle waste as a hydroponic planting medium with a wick system in South Korleko Village. The wick hydroponic system is a simple method that does not require a pump or electricity, making it more energy-efficient and easy to apply. This research aims to introduce hydroponic farming methods with low cost and easy-to-find materials, as well as increase public understanding of hydroponic plant cultivation. The methods used include socialization, training, and hands-on practice in making hydroponic wicks using used plastic bottles and flannel as nutrient absorption axes. Results showed that this system was effective for growing lettuce (Lactuca sativa L.), with good growth in about six weeks. By using AB mix nutrient solution, plants obtain enough nutrients to support their growth. The implementation of this system is expected to help the community in increasing vegetable production, reducing plastic waste, and providing a more efficient alternative to farming.